Alternations of interhemispheric functional connectivity in corneal ulcer patients using voxel-mirrored homotopic connectivity: a resting state fMRI study. (September 2019) - Shi, Wen-Qing; Liu, Jia-Xiang; Yuan, Qing; Ye, Lei; Su, Ting; Jiang, Nan; Lin, Qi; Min, You-Lan; Li, Biao; Zhu, Pei-Wen; Xu, Xiao-Wei; Shao, Yi
Background: Corneal ulcer (CU) is the second ocular disease leading to blindness. Millions of people around the world suffer from CU. However, the relationship between CU and altered functional connectivity in the brain is still unknown. Purpose: The aim of the present study was to investigate the alterations of the brain interhemispheric functional connectivity (FC) in patients with CU using the voxel-mirrored homotopic connectivity (VMHC) method and their relationship with clinical manifestations. Material and Methods: The present study involved 24 patients with CU (12 men, 12 women) and 24 healthy controls (HCs) with their age, sex, and weight closely matched. Independent sample t-test, VMHC method, and Pearson's correlation analysis were applied. Receiver operating characteristic (ROC) curve analysis was used to estimate the effect in distinguishing CU patients from HCs. Results: The CU patients showed decreased VMHC values in bilateral lingual/calcarine, precentral/postcentral gyrus, and medial frontal gyrus compared with HCs. There were positive correlations between Visual Analogue Score (VAS) and VMHC values of bilateral media frontal gyrus ( r  = 0.654, p  = 0.001), the best-corrected VA of the affected eye and VMHC values of the bilateral lingual/calcarine region ( r  = 0.960, p  < 0.001). ROC curve also showed high diagnostic values in those regions. Conclusion: Our study was the first to explore FC changes in CU patients' brains using VMHC methods. We demonstrated that ocular pain of CU patients had a close relationship with altered VMHC values. Decreased VMHC values in the brain of CU patients may be useful markers to reflect the condition of progress in patients with CU.